Sialic acid-binding Ig-like lectin-7 interacts with HIV-1 gp120 and facilitates infection of CD4(pos) T cells and macrophages - Varchetta, Stefania (BioMed Central, 2013)
BACKGROUND: Sialic acid-binding Ig-like lectin-7 (Siglec-7) expression is strongly reduced on natural killer (NK) cells from HIV-1 infected viremic patients. To investigate the mechanism(s) underlying this phenomenon, we hypothesized that Siglec-7 could contribute to the infection of CD4(pos) target cells following its interaction with HIV-1 envelope (Env) glycoprotein 120 (gp120). RESULTS: The ability of Siglec-7 to bind gp120 Env in a sialic acid-dependent manner facilitates the infection of both T cells and monocyte-derived macrophages (MDMs). Indeed, pre-incubation of HIV-1 with soluble Siglec-7 (sSiglec-7) increases the infection rate of CD4(pos) T cells, which do not constitutively express Siglec-7. Conversely, selective blockade of Siglec-7 markedly reduces the degree of HIV-1 infection in Siglec-7(pos) MDMs. Finally, the sSiglec-7 amount is increased in the serum of AIDS patients with high levels of HIV-1 viremia and inversely correlates with CD4(pos) T cell counts. CONCLUSIONS: Our results show that Siglec-7 binds HIV-1 and contributes to enhance the susceptibility to infection of CD4(pos) T cells and MDMs. This phenomenon plays a role in HIV-1 pathogenesis and in disease progression, as suggested by the inverse correlation between high serum level of sSiglec-7 and the low CD4(pos) T cell count observed in AIDS patients in the presence of chronic viral replication.